DETERMINACIÓN DE Escherichia coli 0157 A PARTIR DE PRODUCTOS CÁRNICOS Y LÁCTEOS ARTESANALES EMPLEANDO DOS SISTEMAS DE AISLAMIENTO - Franco Urrutia, Lina; Laboratorio de Microbiología Veterinaria, Departamento de Microbiología, Facultad de Ciencias, Pontificia Universidad Javeriana, Bogotá (2013)
With the intention of determining the presence of E. coli 0157 in foods, in the North zone of the Sabana of Bogotá, 300 artisan meat and milky product samples were analyzed. For their isolation and identification two techniques were used; a traditional one where after six hours of incubation in water peptonada to suplementada 1% with novobiocina (20 mg!L) boards of agar Mac Conkey Sorbitol inoculated. By means of this technique Esclzericlzia coli 0157 from a single sample (0.33%) of 300 analyzed the corresponding one to a meat derivative (hamburger); also E. coli in 1.6% was identified. Sirnultaneously a fast technique with Fluorocult, Agar for E. coli O 157: H7 and of the three hundred isolated samples microorganisms like Esclzericlzia coli 0157 (0.33%), E. coli (25%), Slzigella sonnei (10%), E. aerogenes (9%), P. mirabilis ( 4% ). Of the two tried techniques these presented/displayed the same percentage of recovery of Esclzericlzia coli 0157. The fast method, using Fluorocult, Agar for E. coli 0157: H7 allowed to obtain presuntivos results in 24 hours and confirrning results in 48 hours. In resistance the traditional method using to agar Mac Conkey Sorbitol allowed to obtain presuntivos results in 24 hours and confirmíng results in five days. The methods and used techníques allow that thís study can reproduce easily with precise results.